Unexpected Phase Behavior of Pluronic Polymer-Organic Derivative Mixtures Depending on Temperature in Aqueous Solution - Jong-Dae Jang; Eunhye Kim; Min-Jae Lee; Young-Soo Han; Joona Bang; Tae-Hwan Kim (Micromachines, 2018)
The phase behavior of amphiphilic Pluronic block copolymers in aqueous solution is of importance for a broad spectrum of practical applications but has not been fully exploited yet. Here, the phase behavior of the mixture of the Pluronic P65 and P105 triblock copolymer, (which have the same composition of PEO and PPO but the different molecular weight) and organic derivative, 5-methyl salicylic acid (5mS), in aqueous solution has been investigated by using small angle neutron scattering (SANS). According to the temperature and the 5mS concentration, SANS measurements showed that the P65-5mS mixtures sequentially transform into a random coil, sphere, vesicle, cylinder, and vesicle again, while the P105-5mS mixtures form spherical particles with two different sizes without any topological phase transition. Upon heating, the formation of two different kinds of the vesicle structure of amphiphilic block copolymer in aqueous solution is very unusual. This phase behavior was explained as the coupled effect of the simultaneous increase of the hydrophobicity of the polymer and the solubility of 5mS molecules upon heating. This result gives fundamental information for the practical use of Pluronic polymers in nano- and bio-science and it provides a simple route for the fabrication of the nanostructure without a complicated procedure.